2011
DOI: 10.14214/sf.85
|View full text |Cite
|
Sign up to set email alerts
|

The conservation potential of brook-side key habitats in managed boreal forests

Abstract: Today, maintaining biodiversity is included in the targets of boreal forest management. A widespread approach in northern Europe is to identify and preserve woodland key habitats within managed forests. Woodland key habitats are expected to be patches that host populations of threatened and declining species, and the preservation of these patches is assumed to enable the persistence of the focal species in the landscape. In Finland, the criteria for selecting woodland key habitats are defined in the Finnish Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…), because they are sensitive to changes in soil moisture (Richard, Bernhardt & Bell ) and known indicators of reference‐state riparian forests (Selonen et al . ).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…), because they are sensitive to changes in soil moisture (Richard, Bernhardt & Bell ) and known indicators of reference‐state riparian forests (Selonen et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…We also examined separately the cover of large ferns (Athyrium filix-femina L., Dryopteris carthusiana Vill., Matteuccia struthiopteris L., Phegopteris connectilis Michx. ), because they are sensitive to changes in soil moisture (Richard, Bernhardt & Bell 2000) and known indicators of reference-state riparian forests (Selonen et al 2011).…”
Section: Biological Samplingmentioning
confidence: 99%
“…All of these habitats are terrestrial and the most numerous FAH type is the riparian habitat of the boreal brooks or rivulets (small streams) [7]. Riparian habitats are a heterogeneous mosaic of terrestrial and aquatic habitats, therefore often harbouring a rich biodiversity [8-10]. Small streams themselves and the adjacent riparian habitats appear to be vulnerable and their biodiversity is often adversely influenced by forests management [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in Scots pine forests, Rodriguez and Kouki (2015) showed that, 13 years after felling, blueberry (Vaccinium myrtillus) cover, flowering, and berry production were still lower than in unharvested forest, irrespective of retention level (10 or 50 m 3 ha −1 ), whereas the resilience of lingonberry (Vaccinium vitisidaea) was higher (but see Granath et al 2018). Riparian brook-side forests, studied in the PuroMONTA experiment in central Finland, are important for many rare and red-listed forest species (Selonen et al 2011;Selonen and Kotiaho 2013;Selonen 2014;. This experiment showed that if clear felling is applied in adjacent forests, unharvested buffer zones surrounding brooks must be at least 35-45 m wide to support the initial riparian plant and moss communities.…”
Section: Long-term Responses To Retentionmentioning
confidence: 99%